Manufacturing of Ecofriendly Bricks Using Microdust Cotton Waste - Mebrahtom Teklehaimanot; Haregeweyni Hailay; Tamrat Tesfaye (Journal of Engineering)
Large amounts of cotton microwastes are accumulated in textile industries. The cotton microdust is less to ignite and causes serious environmental problems and health hazards. This paper presents an experimental study, which investigates the potential use of cotton microdust to produce new and lightweight brick for construction industries. The physical and mechanical properties of brick mixes having different levels of cotton microdust ratio were investigated. The test results recorded for compressive strength, unit weight, and water absorption values satisfy the relevant required standards for normal construction bricks. The results show that the replacement of clay soil and cement by cotton microdust does not exhibit a sudden brittle fracture even beyond the failure loads, indicates high energy absorption capacity, reduces the unit weight dramatically, and introduces smother surface compared to the current concrete bricks in the market. The results also show that usage of cotton microdust with different mixing ratios for bricks will give light-weight composite, and brick could be an economical alternative to be used for partition of board concrete blocks and sound barrier panels.